PENERAPAN PERATURAN DENGAN MENGGUNAKAN SIMULASI PARAMETRIK PADA BANGUNAN DAN LINGKUNGAN PERMUKIMAN KAMPUNG SILIWANGI BANDUNG - Lilian Setiawan (Ide dan Dialog Desain Indonesia (Idealog), 2019)
The city of Bandung had a rapid development. The growth and development process of the city is largely determined by the strategy of the government itself. Therefore, the government regulates the direction of urban growth through the formation of regulations. However, the current condition of regulations and arrangement of development are quite worrying. The process applied is not in line with regulations, the quality of the environment decreases because of the illegally grown land use of settlements Covenience in an area is also closely related to the conditions of nature environment. Like the existence of Cikapundung river which is no longer considered. It can be seen in riverside housing that increasingly wild and growing organically. The purpose of this study is to identify the physical arrangement of the environment and buildings in the Cikapundung riverside settlement Bandung and its influence on the application of regulations. The method used is 1) A quantitative approach at the stage of data collection and analysis with parametric simulation technique modeling, using Rhinoceros Grasshopper software; 2) A qualitative approach in forming conclusions relating to the prediction of the building mass compared to the existing conditions. Analysis was carried out based on applicable regulatory studies including Building Coverage Ratio (BCR), Floor Average Ratio (FAR), and River Border Line, then applied to the simulation of building shapes, and identified behavior of the inhabitants. This research is expected to be a guide to the strategy of planning, structuring, and developing architcture especially the building form in riverside settlements. Keywords : Building Regulations, Parametric Simulation, Riverside, Settlement